The non-derivative Russian prepositions in historical lexicography: vectors of semantic comprehension (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
This article studies the understanding of the language nature of prepositions and their prefixes homonymous in the lexicography of XVIII - XIX centuries. The analysis of non-derivative prepositions in dictionaries and grammars of XVIII - XIX centuries reveals the dynamics of understanding the semantics of prepositions and the origins of modern linguistic theories about the nature of the propositional language vocabulary.
Keywords: preposition; word-morpheme; word-sentence; structural analysis; cognitive-onomasiological analysis; functional analysis